A Method of Integral Equations for a Structure in the Form of Thin Elastic Plates - Shuvalova, Yu.S.; Strelnikova, E.A. (Управляющие системы и машины, 2011)
The second basic dynamic problem for thin elastic plates in Kirchhoff model is under consideration. The problem reduces to system of the nonstationary boundary equations by means of dynamic analogue of a single layer potential. The numerical solutions of these systems have been obtained. The investigation of convergence of method of discrete singularities for the plate of the rectangular form have been carried out. Рассмотрена вторая основная задача динамики тонких упругих пластин в рамках модели Кирхгофа. С помощью динамического аналога потенциала простого слоя задача сводится к системе нестационарных граничных уравнений. Получены численные решения этих систем. Исследованы сходимости метода дискретных особенностей для прямоугольной пластины. Розглянуто другу основну задачу динаміки тонких пружних пластин у рамках моделі Кірхгофа. За допомогою динамічного аналога потенціалу простого шару задача зводиться до системи нестаціонарних граничних рівнянь. Одержано чисельні розв’язки цих систем. Досліджено збіжності методу дискретних особливостей для прямокутної пластини.